Promoting low-flow anaesthesia and volatile anaesthetic agent choice. Issue 3 (13th September 2019) - Carter, Louise A; Oyewole, Molola; Bates, Eleanor; Sherratt, Kate
Abstract : Background: As doctors, we are increasingly aware of the financial implications of our practice. The need to work in a more conscientious, efficacious and cost-effective manner is greater than ever before. Environmental and financial benefits can be seen through employing the use of low-flow anaesthesia. Aims: This quality improvement project aimed to make anaesthetic practice more environmentally friendly and to reduce departmental spending. This could be achieved by promoting the use of low-flow anaesthesia and by encouraging isoflurane use where appropriate. Methods: All anaesthetic consultants and trainees were invited to fill out an initial questionnaire relating to their personal preferences and practices when conducting anaesthesia. There were specific questions relating to low-flow anaesthesia and isoflurane use. Our main measure of improvement was any decrease in the number of bottles of volatile agent ordered by the department from pharmacy. Monthly spot audits were conducted to assess gas flow rates and volatile agent use in theatre. Departmental spending figures relating to the purchase of volatile agent bottles were obtained from pharmacy. Information was then disseminated to anaesthetists on a monthly basis via a 'low-flow board', which showed pictorial and graphical representations of differing gas flows and volatile agent usage in relation to cost. Results: Our project showed a trend for the increased use of low-flow anaesthesia within the department. We also showed a decrease in the number of bottles of volatile agent ordered: 18% fewer bottles ordered compared with the same period the previous year. This represented a 25% decrease in total departmental expenditure on volatile agents despite an increase in theatre activity. Conclusion: Increasing awareness regarding anaesthetic choices and promoting low-flow anaesthesia and isoflurane use, translated into an overall decreased departmental spend on volatile agents without affecting patient care.